2021
DOI: 10.1016/j.clnesp.2021.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Hospital nutrition care informs potential cost-savings for healthcare: A budget impact analysis

Abstract: Background and aim: In Mexico, about half of hospitalized patients are malnourished or at risk of malnutrition upon hospital admission, while many others experience deterioration of their nutritional status while in the hospital. Such patients often experience poor health outcomes and have increased hospital costs. The aim of our budget-impact analysis was to estimate potential savings associated with the implementation of a Mexican hospital-based program of nutrition care for patients at malnutrition risk or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…When the body is infected, the body will need various nutrients more. [ 64 ] In a recent study Calder et al . [ 65 ] revealed that providing balanced nutrition is critical for improving the immune responses against viral infection.…”
Section: Methodsmentioning
confidence: 99%
“…When the body is infected, the body will need various nutrients more. [ 64 ] In a recent study Calder et al . [ 65 ] revealed that providing balanced nutrition is critical for improving the immune responses against viral infection.…”
Section: Methodsmentioning
confidence: 99%
“…En la actualidad existe evidencia de que la DAE puede ser una entidad clínica tratada con intervenciones costoefectivas, tanto para el paciente como para las instituciones, cuyo ahorro proyectado por paciente es hasta 41,5 % menos con terapia nutricional temprana, así como 23,8 % menos en costos de hospitalización y 66,4 % menos en costos de readmisiones. Esto representa un ahorro anual en salud pública de hasta 32,1 % (12) .…”
Section: Justicia: Oportunidad Justa E Igualitariaunclassified
“…There are multiple forms of malnutrition and most of them are extremely difficult to assess in a reliable manner, because of complex interactive environments characterized by a high number of uncertainties. This hurdle can be circumvented by conducting health-economic evaluations in the hospital setting, which ensures meaningful outcomes for further exploitation as reported for other Low- or Middle-Income Country (LMIC) regions (2;1012). Furthermore, when considering a future multi-country clinical protocol on HMN, it is crucial to identify commonalities and differences among national African healthcare systems.…”
Section: Introductionmentioning
confidence: 99%